Sebuah Studi Psikologis Terhadap Proses Idolisasi Remaja Terhadap Idola K-Pop (Korean Pop) - Hanno Avila Pradata (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2019)
This research based on K-pop music phenomenon which a trend among Indonesian’s teenagers. The beginning process, what idol meant to fans and their impact on fans’ life are the focuses on this research. This research uses qualitative methods and interpretive phenomenological analysis as design. Research shows that there was a stimulation to began the musical interest from the family and this stimulation grows as reinforcement, given especially by mother’s side. There's also obstacles that came from father’s side which reacted by participants by crying and lying. Participants said that emotional and instrumental support given by family or friends, reinforced ther idolization behaviour but they also received bullying from their school’s mate because their K-pop idols looked so feminine. Participant’s fanatism to idols was reinforced and led to a condition called internalization. This internalization condition led them to have sexual fantasies towards the idol and beliefs that idols are their boyfriends.